Boundary Spanning Activities of Corporate HQ Executives Insights from a Longitudinal Study. (19th January 2017) - Birkinshaw, Julian; Ambos, Tina C.; Bouquet, Cyril
Abstract: What are the boundary spanning activities undertaken by the Corporate Headquarters (HQ) executives of a Multinational Corporation? We address this question through a five‐year longitudinal case study of one company as it shifted from a traditional HQ in one location, to a dual HQ in two locations, to a virtual HQ split across multiple locations. By observing how HQ executives prioritized their time over the course of this transition, we identified four generic boundary spanning activities: two ( spearheading and facilitating ) focused on making connections across boundaries, two ( reconciling and lubricating ) focused on overcoming differences in worldview across boundaries. By considering these activities together, and how they vary in importance over time, we show how each boundary spanning activity adds value to the MNC and improves the effectiveness of the internal and external network. An important feature of our study is that we operationalize boundary spanning at the activity level, i.e., in terms of the specific actions taken by corporate HQ executives, to provide a more granular understanding of how boundary spanning works in practice.